Selective Catalytic Reduction of NO by NH3 Over Ceria: Effect of Calcination Temperature on the Activity of Catalysts - Guo1, Rui-Tang; Zhen1, Wen-Long; Zhou1, Yue; Guo Pan1, Wei; Xu2, Hong-Jian; Jin2, Qiang; Ding2, Cheng-Gang; Guo2, Shi-Yi (Asian Journal of Chemistry, 2014)
Ceria was investigated as a catalyst for selective catalytic reduction of NO by NH3. The ceria catalysts were prepared by citric acid method with different calcination temperature. Experimental results showed that the selective catalytic reduction activity of ceria catalyst decreases with increasing calcination temperature within the reaction temperature range of 150-350 ºC. As can be seen from the characterization results of BET, XRD, temperature programmed reduction, total programmed desorption and XPS, the best selective catalytic reduction performance of ceria catalyst calcinated at 350 ºC may be resulted from its large surface area, good redox ability, strong NH3 adsorption capacity and high concentration of active oxygen species on the surface of this catalyst.